Research on the Sugarcane Stubble Chopping Mechanism of an Ultra-Deep Vertical Rotary Tillage Cutter Based on FEM-SPH Coupling Method - Wang Yang; Huangsheng Lu; Xiong Xiao; Zhengkai Luo; Weilong Dai; Zhiheng Lu (Agriculture)
After existing ultra-deep vertical rotary tillers work in sugarcane stubble fields, the stubble chopping performance is poor, and the reason for this is unknown. To solve this, this paper develops a simulation model of ultra-deep vertical rotary tillage (UDVRT) in a sugarcane stubble field using the FEM-SPH coupling method and physical testing. The simulation model is used to investigate the rotary tillage process in the stubble field and the stubble chopping mechanism of the UDVRT cutter, identifying the causes of inadequate stubble chopping effectiveness. The results show that, when comparing the simulation with the field test, the magnitude and variation of the cutter’s torque curves are relatively consistent, the relative error of the topsoil fragmentation rate is 9.5%, the entire cultivated layer of soil fragmentation rate is 11.3%, and the average number of times the stubble stem was cut off is closer; thus, the modeling method of the simulation model is reasonable and accurate. When the cutter cuts the soil and the stubble simultaneously, the soil’s constraint on the stubble is gradually weakened, the velocity difference between the blade and the stem becomes smaller, the tilt of the stems becomes larger, and the number of times the blade can cut the stems reduces, leading to the poor chopping effect of stubble. The cutter cuts the stubble in the order of the blade from top to bottom, with the blade cutting the stem first and then the root, which is an effective measure to increase the stubble fragmentation rate. The findings of this paper can provide a reliable theoretical basis for the optimal design of a UDVRT cutter.